Availability, Reliability and Security for Business, Enterprise and Health Information Systems IFIP WG 8.4/8.9 International Cross Domain Conference and Workshop, ARES 2011, Vienna, Austria, August 22-26, 2011. Proceedings - Tjoa, A Min; Quirchmayr, Gerald; You, Ilsun; Xu, Lida (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the IFIP WG 8.4/8.9 International Cross Domain Conference and Workshop on Availability, Reliability and Security - Multidisciplinary Research and Practice for Business, Enterprise and Health Information Systems, ARGES 2011, held in Vienna, Austria, in August 2011.The 29 revised papers presented were carefully reviewed and selected for inclusion in the volume. The papers concentrate on the many aspects of availability, reliability and security for information systems as a discipline bridging the application fields and the well-defined computer science field. They are organized in three sections: multidisciplinary research and practice for business, enterprise and health information systems; massive information sharing and integration and electronic healthcare; and papers from the colocated International Workshop on Security and Cognitive Informatics for Homeland Defense.